INTEGRASI REGIONAL: ARUS INVESTASI DAN IMPLIKASINYA TERHADAP PENERIMAAN PAJAK - Ferry Irawan; muhammad temmy Putra Fachrezzy (Jurnalku, 2021)
The ASEAN Economic Community (AEC) has been established for several decades. The AEC is inspired by other regional communities. The situation strengthens each country’ economic and investment. Based on ASEAN Statistical Yearbook 2020, in 2019 the capital inflow to ASEAN amounted USD 158 Billion. The objective of this study is to investigate the cause and effect of these global phenomenon to ASEAN countries especially Indonesia. Also, this paper will elaborate FDI effect from the tax revenue point of view. This paper uses a qualitative method in order to obtain a deep understanding. We found several findings. First, there is a relation between the establishment of regional community and foreign direct investment (FDI). Second, FDI is beneficial to enhance the tax administration system especially country’s tax revenue.